A few issues explaining couloir details regarding the assassination of Erekles European ambassadors - Natsvaladze, Mamuka (COLLECTION OF SCIENTIFIC WORKS OF SOKHUMI UNIVERSITY, 2023)
Over the years 1781-82 Erekle II sends his ambassadors to Europe twice: first he sends a Capuchin monk Domenique who dies in Constantinople in uncertain circumstances not having reached the destination; after him Erekle II sends another Capuchin Mauro the Veronese who also dies for unknown reasons while still on his way. It is a very important fact that the letters sent by the King Erekle, unlike the ambassadors, reach their destination which is the Emperor’s Court in Austria. Purpose of the current article is to find out whether it is accidental that none of the Ambassadors of Erekle reached their place of destination and what was the reason for it – assassination of the ambassadors or their natural death. Based on the analysis of facts related to the Ambassade, political situation and letter of Erekle II preserved in the State Archive of Austria, we can conclude that in both cases, it was a diplomatic assassination and not an accident. It is quite suspicious that the next year Erekle sends Mauro Veroneli to Vienna with the same purpose, but through Russia and not Constantinople. The change of the approved route must have been considered by Erekle because of the assassination of the ambassador. With this performance, Erekle explicitly indicates to Russia that his Ambassade does not contain anti-Russian sentiments. There is a primary source confirming that the first Ambassade sent by Erekle had a supervisor interested in disrupting it as well as in the death of Domenico. This period, 1782, is linked to the official report of Catherine II sent to Chancellor Bezborodko in which the Russian Empress confirms that Erekle’s relations with the Emperor of Austria was not desirable and Erekle should stop and refuse the referred correspondence. Based on the mentioned report we can explicitly assume that the Russian Imperial Court was interested in the failure of Ambassade. Accordingly, those diplomatic assassinations were ordered by the latter. Both ambassadors of Erekle were assassinated because they were instructed to orally report the Emperor of Austria the things not mentioned in the letters sent officially. Therefore, the both Capuchin Ambassadors rather than the letters sent by Erekle, were aimed by the Russian Imperial Court. As for the issues to be spoken by the Ambassadors of Erekle with the Emperor of Austria, they are clearly linked to the plan for the redistribution of Europe, developed at the imperial courts of Vienna and St. Petersburg to neutralize the Ottoman Empire. This project could not have been implemented without taking into account the Caucasian factor and Erekle strived to be the participant of this International Project accordingly, as the ruler of a sovereign state. The Russian Imperial Court did not recognize Erekle to be the King of a Sovereign State. The realization of the “Greek Project” would create a Christian global space in the south of the Caucasus, which was a guarantee for the security of Georgia and had always been the dream of all Georgian Kings.